Precalculus: Mathematics for Calculus, 7th Edition

Published by Brooks Cole
ISBN 10: 1305071751
ISBN 13: 978-1-30507-175-9

Chapter 1 - Section 1.3 - Algebraic Expressions - 1.3 Exercises: 87

Answer

$5x^{3}+x^{2}+5x+1=(x^{2}+1)(5x+1)$

Work Step by Step

$5x^{3}+x^{2}+5x+1$ Group the first two terms together. Do the same with the last two terms: $5x^{3}+x^{2}+5x+1=(5x^{3}+x^{2})+(5x+1)=...$ Take out common factor $x^{2}$ from the first parentheses: $...=x^{2}(5x+1)+(5x+1)=...$ Finally, take out common factor $(5x+1)$: $...=(x^{2}+1)(5x+1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.